Challenges of applying IFRS 16 to the Iraqi environment and its role in improving Financial indicators of economic units Applied to the General Company of Iraqi Airways - سلمان عامر محمد; جاري احمد سعد (Journal of Economics and Administrative Sciences, 2025)
Abstract The leases, are regarded as one of the most controversial accounting issues in recent years, since they represents one of the important sources of funding, which may be exploited by the tenant as off- Balance sheet Financing , which negatively affects the quality of financial reporting. The Financial Accounting Standards Board (FASB) and the International Accounting Standards Board (IASB) have "significant" interest in accounting for leases . FASB issued Statement of Financial Accounting Standards 13 on lease contracts in 1976 and IASB issued IAS 17 in 1980, which was amended in 1997 and IFRS 16, issued in January 2016, which will be effective on January 1, 2019 , to solve the problems of leases, especially the operational lease contracts (used in Iraq) of off- Balance sheet Financing . for the lessee. No accounting standard in Iraq has been issued in accordance with the International Standard concerning Tenancy Contracts. Therefore, the aim of the research is to adopt the standard of IFRS 16 according to the specificity of the Iraqi environment and to meet the challenges of implementation and in accordance with Iraq’s approach to the adoption of accounting standards. and the impact on the quality of financial reporting reflected in the financial indicators of economic units leased to the Iraqi environment .The research reached a number of conclusions, the most important of which are the following: - The IFRS 16 standard reflects the accuracy of the IASB’s application of transparency in the financial reporting of the economic units engaged in the leasing activity and the increased understanding and comparability of the users of the financial statements by reflecting the requirements of IFRS 16 for the quality of the financial information. - There are challenges facing the Iraqi environment to adopt financial reporting standards on handling lease contracts. - The adoption of IFRS16 in the Iraqi environment through the proposed model of the General Company of Iraqi Airways has contributed to improving the financial indicators of the company in terms of the quality of information and presentation of the financial statements, which reflects positively "in the decisions of investors and lenders, which is in line with the State’s tendency to attract investment and revitalization Economic movement. The most important recommendations reached by the research are: - The cultural, legislative or economic challenges should be met in order to adopt the criteria for financial reporting of leases in the Iraqi environment through the amendment or enactment of some laws (the law of leasing, tax laws, corporate law). - Trying to formulate accounting models that adopt international standards after adapting them to suit the Iraqi environment to enforce the investigation of articles (25.26) of the Iraqi constitution..